2018
DOI: 10.1002/iub.1984
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rd Inhibits the Metastasis of Colorectal Cancer via Epidermal Growth Factor Receptor Signaling Axis

Abstract: Ginsenoside Rd is a saponin from ginseng and has been reported to have various biological activities. However, the effect of ginsenoside Rd on the metastasis of colorectal cancer (CRC) remains unknown. Here, we found that ginsenoside Rd decreased the colony‐forming ability, migration, invasion, and wound‐healing abilities of CRC cells, although it did not affect cell proliferation. In addition, using an inverse‐docking assay, we found that ginsenoside Rd bound to epidermal growth factor receptor (EGFR) with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…Intestinal enzymes can metabolize high content GSRb1 to GSRd, which can then be absorbed and used by the body. Studies have shown that GSRd has strong biological activity and shows unique protective effects on the cardiovascular system ( Zhang et al, 2019 ), immune system ( Zhu et al, 2014 ), alimentary system ( Liu et al, 2018 ; Phi et al, 2019 ), and central nervous system ( Cong and Chen, 2016 ). Several animal studies have shown that GSRd can improve motor system function, reduce striatum injury area and cerebral infarction volume, have neurotrophic and protective effects on neurodegenerative diseases, such as Alzheimer’s disease and Parkinson’s disease, and improve neurological dysfunction caused by ischemic stroke ( Ye et al, 2009 ; Wang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal enzymes can metabolize high content GSRb1 to GSRd, which can then be absorbed and used by the body. Studies have shown that GSRd has strong biological activity and shows unique protective effects on the cardiovascular system ( Zhang et al, 2019 ), immune system ( Zhu et al, 2014 ), alimentary system ( Liu et al, 2018 ; Phi et al, 2019 ), and central nervous system ( Cong and Chen, 2016 ). Several animal studies have shown that GSRd can improve motor system function, reduce striatum injury area and cerebral infarction volume, have neurotrophic and protective effects on neurodegenerative diseases, such as Alzheimer’s disease and Parkinson’s disease, and improve neurological dysfunction caused by ischemic stroke ( Ye et al, 2009 ; Wang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with previous studies, which reported that TLR2 was a direct target of miR-144-5p and miR-144-5p down-regulated TLR2 expression. 10,11) Herein, the GS-Rd/miR-144-5p/TLR2 axis was established. Subsequently, this axis was verified by TLR2 expression, as detected by Western blotting and RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…The result was consistent with a previous study. 11) Effect of GS-Rd and miR-144-5p on TLR2 Expression in U251 and U87 Cells The GS-Rd/miR-144-5p/TLR2 nexus was investigated by RT-qPCR and Western blot in the following experiments. The TLR2 mRNA levels were found to be up-regulated in untreated U251 and U87 cells compared with normal human astrocytes (NHA) (Fig.…”
Section: Expression Of Mir-144-5p In Human Glioblastoma Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were fed with an HFD (D12492; Research Diets, New Brunswick, New Jersey) to establish DIO models. Rd intraperitoneal injection dose usually ranges from 5 to 100 mg/kg/day in mice . Our preliminary experimental results showed that Rd could not significantly improve obesity until the injection dose was as high as 15 mg/kg/day (data not shown), and therefore we decided that the DIO mice would be administered an intraperitoneal injection of 15 mg/kg of Rd or phosphate‐buffered saline (PBS) (vehicle) daily.…”
Section: Methodsmentioning
confidence: 99%